Competing Explanations of Competing Explanations: Accounting for Conflict Between Scientific and Folk Explanations. (25th November 2019) - Shtulman, Andrew; Legare, Cristine H.
Abstract: People who hold scientific explanations for natural phenomena also hold folk explanations, and the two types of explanations compete under some circumstances. Here, we explore the question of why folk explanations persist in the face of a well‐understood scientific alternative, a phenomenon known as explanatory coexistence . We consider two accounts: an associative account, where coexistence is driven by low‐level associations between co‐occurring ideas in experience or discourse, and a theory‐based account, where coexistence reflects high‐level competition between distinct sets of causal expectations. We present data that assess the relative contributions of these two accounts to the cognitive conflict elicited by counterintuitive scientific ideas. Participants (134 college undergraduates) verified scientific statements like "air has weight" and "bacteria have DNA" as quickly as possible, and we examined the speed and accuracy of their verifications in relation to measures of associative information (lexical co‐occurrence of the statements' subjects and predicates) and theory‐based expectations (ratings of whether the statements' subjects possess theory‐relevant attributes). Both measures explained a significant amount of variance in participants' responses, but the theory‐based measures explained three to five times more. These data suggest that the cognitive conflict elicited by counterintuitive scientific ideas typically arises from competing theories and that such ideas might be made more intuitive by strengthening scientific theories or weakening folk theories. Abstract : Competing Explanations of Competing Explanations: Accounting for Conflict Between Scientific and Folk Explanations This paper focuses on the level of people's explanatory reasoning. It examines why laypeople prefer folk explanations of various physical or biological phenomena to alternative, well‐understood scientific explanations. Shtulman and Legare call this psychological phenomenon "explanatory co‐existence." On the basis of new experimental data, they evaluate two possible accounts of explanatory co‐existence, a theory‐based and an associative account, and argue that a theory‐based account is the better supported.